Bounded solutions of a system of linear inhomogeneous differential equations of the first order with rectangular matrices - Boichuk, A. A.; Elishevich, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.926.7 Conditions for existence are determined and bounded solutions of a system of linear inhomogeneous differential equations of the first order with rectangular matrices are constructed.